High-speed inter-city transport system in Japan: Past, present and the future - Katsuhiro Yamaguchi; Kiyoshi Yamasaki (Organisation for Economic Co-operation and Development (OECD), Joint Transport Research Centre (JTRC), 2009)
With the advent of Shinkansen in 1964, a unique inter-city transport network in which high-speed railway and air transport developed simultaneously, emerged in Japan, and modal choice between them based on price and speed has been manifested. Looking ahead, the next generation high-speed transport, the Maglev, is on the horizon. In order to capture the full impacts of the Maglev technology, simulation analysis with a dynamic spatial nested logit model was conducted. From this, we identified a significant opportunity for the Maglev Super-express between Tokyo, Nagoya and Osaka, but with net benefitsexceeding net costs only with an annual economic growth of approximately 2% - 3% achieved in the next 65 years in Japan. If such economic condition were realized, the total air transport market would also continue to grow despite strong competition from the Shinkansen/Maglev system. Another point of interest is Maglev's impact on reducing global warming. CO2 emission from Maglev is one-third of air transport. Introduction of Maglev Super-express in inter-city transport, however, also attracts passengers from Shinkansen that has five times lower CO2 emission intensity. Indeed, our simulation analysis shows that total CO2 emissions from high-speed inter-city transport increases when Maglev Super-express is introduced. Increase in total CO2 emission from electricity users including Maglev Super-express could be mitigated by energy conversion sector's effort to reduce CO2 content of electric power supply, for instance, by increasing utilization of nuclear energy. Further research in assessing possible impact of capacity constraint in existing network, not considered in this paper, would facilitate deeper understanding of the future high-speed inter-city transport system.
Keywords: 330